Experimental, numerical and parametric studies on stress concentration factors of T-joints under tension. Issue 2 (January 2022) - Matti, Feleb; Mashiri, Fidelis
This paper investigates the behaviour of square hollow section (SHS) T-joints under static axial tension for the determination of stress concentration factors (SCFs) at the hot spot locations. Five empty and corresponding concrete-filled SHS-SHS T-joint connections were tested experimentally and numerically. The experimental investigation was carried out by attaching strain gauges onto the SHS-SHS T-joint specimens. The numerical study was then conducted by developing three-dimensional finite element (FE) T-joint models using ABAQUS finite element analysis software for capturing the distribution of the SCFs at the hot spot locations. The results showed that there is a good agreement between the experimental and numerical SCFs. A series of formulae for the prediction of SCF in concrete-filled SHS T-joints under tension were proposed, and good agreement was achieved between the maximum SCFs in SHS T-joints calculated from FE T-joint models and those from the predicted formulae.